2019
DOI: 10.1039/c9ra06581d
|View full text |Cite
|
Sign up to set email alerts
|

A nanoscopic icosahedral {Mo72Fe30} cluster catalyzes the aerobic synthesis of benzimidazoles

Abstract: Catalytic activity of amorphous {Mo72Fe30} nanoclusters as a safe Keplerate polyoxometalate in aerobic synthesis of benzimidazoles was described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 45 publications
0
11
0
2
Order By: Relevance
“…POMs with a Keplerate structure are giant metal-oxide-based spherical clusters in which 12 pentagonal [(Mo)–Mo 5 O 21 (H 2 O) 6 ] 6– units are linked to each other by 30 linkers such as {Mo V 2 O 4 }, producing a water-soluble spherical {Mo 132 }. The use of Cr III aq and Fe III aq as linkers generates mixed metal Keplerates {Mo 72 M 30 } (M = Cr, Fe) exhibiting unique optical, electronic, and magnetic properties. , They are attractive materials in diverse disciplines, such as chemistry, physics, magnetism, medical sciences, materials science, nanoscience, and even mathematics. Although catalysis and photocatalysis are well-developed in the POMs community, to our knowledge, the catalysis and particularly photocatalysis by Keplerate are still unknown. The crystallinity, morphology, and consequently solubility of some Keplerates could be easily controlled by synthetic procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…POMs with a Keplerate structure are giant metal-oxide-based spherical clusters in which 12 pentagonal [(Mo)–Mo 5 O 21 (H 2 O) 6 ] 6– units are linked to each other by 30 linkers such as {Mo V 2 O 4 }, producing a water-soluble spherical {Mo 132 }. The use of Cr III aq and Fe III aq as linkers generates mixed metal Keplerates {Mo 72 M 30 } (M = Cr, Fe) exhibiting unique optical, electronic, and magnetic properties. , They are attractive materials in diverse disciplines, such as chemistry, physics, magnetism, medical sciences, materials science, nanoscience, and even mathematics. Although catalysis and photocatalysis are well-developed in the POMs community, to our knowledge, the catalysis and particularly photocatalysis by Keplerate are still unknown. The crystallinity, morphology, and consequently solubility of some Keplerates could be easily controlled by synthetic procedures.…”
Section: Introductionmentioning
confidence: 99%
“…However, the greater disorder in the structure of amorphous materials and structural differences between two forms of {Mo 72 Fe 30 } clusters should be taken into account. Encouraged by our promising results on the catalytic activity of Keplerates and recent findings on the catalytic and photocatalytic activity of amorphous {Mo 72 Fe 30 }, , in this work, we wish to evaluate the photocatalytic potential of amorphous {Mo 72 Fe 30 } for visible/sun-light-driven photodegradation of organic dyes as persistent organic pollutants (POPs), a very active research area in recent decades . Different cationic and anionic organic dyes were efficiently removed from water under sunlight within 1 h using a catalytic amount of the amorphous cluster acting as a heterogeneous photocatalyst in combination with dye molecules (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we were very keen to investigate whether such an inexpensive and instantly isolated nanomaterial had some meaningful applications. In the meantime, Rezaeifard, Jafarpour, and their co-workers from the Catalysis Research Laboratory of University of Birjand have shown that this amorphous nanomaterial {Mo 72 Fe 30 } NM is quite superior to crystalline {Mo 72 Fe 30 } cryst as far as the photocatalytic performances toward the degradation of organic dyes and a catalase like activity, including an aerobic synthesis of benzimidazoles, are concerned. Recently, Supriya and co-workers performed proton conductivity studies on {Mo 72 Fe 30 } cryst , and they have even extended their studies to determine the photochromism properties of the {Mo 72 Fe 30 }-type keplerate. , In the last several years, we have been working on electrocatalytic water splitting, , an important and contemporary research goal at the moment worldwide (due to the energy crisis issue on our planet Earth). Since this amorphous substance, Na 2 [Mo 72 Fe 30 O 252 ­(CH 3 COO) 4 ­(OH) 16 ­(H 2 O) 108 ]·180H 2 O ({ Mo 72 Fe 30 } NM ), is water insoluble, having 16 hydroxyl groups per {Mo 72 Fe 30 } cluster, in contrast to its crystalline analogue, [Mo 72 Fe 30 O 252 ­(CH 3 COO) 12 ­{Mo 2 O 7 (H 2 O)} 2 ­{H 2 Mo 2 O 8 (H 2 O)}­(H 2 O) 91 ]·150H 2 O ( {Mo 72 Fe 30 } cryst ) and the Müller group established that a guest-free {Mo 72 Fe 30 } cluster cage can be reduced by two electrons that are delocalized over 72 Mo ions on the cage surface retaining its structural integrity, the substance {Mo 72 Fe 30 } NM has the potential to act as a heterogeneous electrocatalyst for water reduction to yield molecular hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Пористый сферический нанокластерный полиоксометаллат (ПОМ) с уникальной структурой кеплератного типа [1,2] , как и родственные кеплератные структуры, представляет интерес в различных областях, таких как биомедицинская отрасль [3][4][5]. Указывается на его применимость в катализе [6,7]. Находящийся в растворах ПОМ, катализирует, в частности, фотоинициируемую реакцию разложения пероксида водорода [6], а также более сложные реакции синтеза.…”
Section: Introductionunclassified
“…Находящийся в растворах ПОМ, катализирует, в частности, фотоинициируемую реакцию разложения пероксида водорода [6], а также более сложные реакции синтеза. Это относится, например, к получению бензамидозолов [7]. Соединения железа являются катализаторами реакций окисления органических соединений, известными, в частности, как реакции Фентона [8].…”
Section: Introductionunclassified